Model Aplikasi E-Litbang di Lingkup Pemerintah Kota Bandung - Pratama Noor Apria; Septiana Dwi Putrianti; Abdul Rahman (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
The problems of a city, especially the city of Bandung have developed so complex that conventional solutions are often no longer able to catch up with the speed of growth of problems, more innovative solutions (Smart City) are needed to solve city problems, ICT (Information and Communication Technology) is one alternative solutions that have very high innovative potential to solve various urban challenges. One solutive idea to solve problems in the city of Bandung, is by presenting the Bandung Smart City Policy, where this Policy contains programs and directions from the Government of the City of Bandung to change the habits and lifestyle of the Bandung City People who were traditional and tend to be stiff in their daily lives, becoming more modern mindset one step further by promoting the digitalization of information and communication technology in running the wheels of people's daily lives. One of the supporting media for the Bandung Smart City Policy is innovation. Application Model of E-Litbang is presented as a media for monitoring and evaluating all innovation products, how long the level of use of an innovation product, how far the level of understanding of supporting human resources and the community of an innovation product, how good the quality of an innovation product, and how many benefits are generated from an innovation product for wide audience.